Rancang Bangun Sistem Informasi Permintaan Pembelian Barang Berbasis Web Di Stmik Stikom Surabaya - Pranata, Galih Ariadhi; Tanuwijaya, Haryanto; Sudarmaningtyas, Pantjawati (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2014)
Abstract: The problem that occurred was at the time of demand for goods, which requests approval is done by signing the request form, so it requires the presence of the person concerned, but that happens the person concerned does not always be in place, as well as the absence of a reporting system requests the purchase of goods, supplies requests and stock supplies in warehouses that serve as a reference in the purchase of goods and supplies data summary of all the divisions that still have to be calculated again by the division of General Administration. In the research phase using System Development Life Cycle. The trials of the system and user involving several divisions, based on the results of such trials demand for information systems web-based purchases in STMIK STIKOM Surabaya able to produce design information systems that can manage the demand for the purchase of goods with a digital signature as the authentication approval as well as part of General Administration to determine report goods purchase request, request supplies, stock supplies in warehouses and supplies data summary of all the divisions.